Enterohemorrhagic Escherichia coli as causes of hemolytic uremic syndrome in the Czech Republic. - Monika Marejková; Květa Bláhová; Jan Janda; Angelika Fruth; Petr Petráš (PLoS ONE, 2013)
BACKGROUND: Enterohemorrhagic Escherichia coli (EHEC) cause diarrhea-associated hemolytic uremic syndrome (D+ HUS) worldwide, but no systematic study of EHEC as the causative agents of HUS was performed in the Czech Republic. We analyzed stools of all patients with D+ HUS in the Czech Republic between 1998 and 2012 for evidence of EHEC infection. We determined virulence profiles, phenotypes, antimicrobial susceptibilities and phylogeny of the EHEC isolates. METHODOLOGY/PRINCIPAL FINDINGS: Virulence loci were identified using PCR, phenotypes and antimicrobial susceptibilities were determined using standard procedures, and phylogeny was assessed using multilocus sequence typing. During the 15-year period, EHEC were isolated from stools of 39 (69.4%) of 56 patients. The strains belonged to serotypes [fliC types] O157:H7/NM[fliC(H7)] (50% of which were sorbitol-fermenting; SF), O26:H11/NM[fliC(H11)], O55:NM[fliC(H7)], O111:NM[fliC(H8)], O145:H28[fliC(H28)], O172:NM[fliC(H25)], and Orough:NM[fliC(H250]. O26:H11/NM[fliC(H11)] was the most common serotype associated with HUS (41% isolates). Five stx genotypes were identified, the most frequent being stx(2a) (71.1% isolates). Most strains contained EHEC-hlyA encoding EHEC hemolysin, and a subset (all SF O157:NM and one O157:H7) harbored cdt-V encoding cytolethal distending toxin. espPα encoding serine protease EspPα was found in EHEC O157:H7, O26:H11/NM, and O145:H28, whereas O172:NM and Orough:NM strains contained espPγ. All isolates contained eae encoding adhesin intimin, which belonged to subtypes β (O26), γ (O55, O145, O157), γ2/θ (O111), and ε (O172, Orough). Loci encoding other adhesins (efa1, lpfA(O26), lpfA(O157OI-141), lpfA(O157OI-154), iha) were usually associated with particular serotypes. Phylogenetic analysis demonstrated nine sequence types (STs) which correlated with serotypes. Of these, two STs (ST660 and ST1595) were not found in HUS-associated EHEC before. CONCLUSIONS/SIGNIFICANCE: EHEC strains, including O157:H7 and non-O157:H7, are frequent causes of D+ HUS in the Czech Republic. Identification of unusual EHEC serotypes/STs causing HUS calls for establishment of an European collection of HUS-associated EHEC, enabling to study properties and evolution of these important pathogens.